(Il)Legal Violence at the Border: A Comparative Analysis of LGBTQ+ Asylum Claims in the United States and Europe - Amanda Lack (Washington University Journal of Law and Policy, 2022)
An estimated 175 million LGBTQ+ individuals worldwide live under persecutory environments. As highly controversial conversations regarding issues of sexuality are taking place in the context of current unprecedented global population movements, masses of LGBTQ+ individuals are fleeing their home countries in hopes of international protection in safer environments. Researchers estimate, however, that fewer than 2,500 LGBTQ+ refugees a year are accorded protection globally. This Note engages in a comparative analysis of LGBTQ+ asylum claims in the United States and Europe. The author’s analysis highlights the shortcomings of the asylum systems with regard to proving the credibility of LGBTQ+ asylum claims, being “gay enough,” and the applicability of LGBTQ+ asylum frameworks to all ‘letters’ of the acronym. To remedy these shortcomings, the author proposes a series of policy-based suggestions that advocate for the protection and furtherance of LGBTQ+ refugee and asylee rights both nationally and internationally.
Keywords: LGBTQ+ Asylum Claims; LGBTQ+ Refugees